Tobacco endgame policies: an analysis of preferred strategies and support levels in a sample from Qatar - Aisha Al-Naimi; Khadiga Elsayed; Marwa Alharoon; Fatma Al-Obaidli; Hissa Almuraikhi; Amaal Osman; Reem Al-Rashdi; Mujahed Shraim; Mohammed Al-Hamdani (Frontiers in Public Health)
BackgroundThere is limited evidence on preferences for tobacco endgame policies and support levels for them in the Middle East. Further, no studies on the interactive association of sex and tobacco use status with support levels exist to date.ObjectivesTo examine preferred tobacco endgame strategies and levels of support in a Qatari sample.MethodsA convenience sample of adults (N = 372; 73.3% females) completed a cross sectional survey. Preferences for strategies were assessed by demographic variables using chi-square tests and levels of support were compared by sex and tobacco use status while adjusting for other factors using bootstrapped regression.ResultsMales and current tobacco users prefer standardized packages, females prefer nicotine reduction policies, and never tobacco users prefer tax increases, import bans, bans for minors and adults, and flavor bans. Never and past tobacco users reported higher tobacco endgame support relative to current tobacco users. Further, males who never used tobacco or used it in the past reported higher tobacco endgame support than male current users.ConclusionHigh tobacco endgame support level and preferences for a wide range of tobacco endgame policies might be promising indicators for embracing them, especially among never tobacco users and males that do not currently use tobacco in Qatar.